Kinetic and mechanistic studies of oxygen sensing Fe(II)/2-oxoglutarate dependent oxygenases - Tarhonskaya, H (2014)
The Fe(II)/2-oxoglutarate (2OG) dependent oxygenases are a widespread enzyme family, which are characterised by structurally similar active sites and proposed to employ a common reaction mechanism. The work described in this thesis concerned kinetic and biophysical studies on 2OG oxygenases, with a particular focus on the hypoxia-inducible transcription factor (HIF) hydroxylases and mechanistic aspects of their reaction with oxygen. The four human HIF hydroxylases regulate cellular levels and transcriptional activity of HIF by catalysing its post-translational hydroxylation in response to changes in oxygen availability. The three prolyl hydroxylase domain enzymes (PHDs1-3) and factor inhibiting HIF (FIH) are proposed to act as cellular oxygen sensors and provide a direct link between oxygen availability and the hypoxic response. Previous transient kinetic studies have shown that PHD2 (the most important human PHD isoform) reacts slowly with oxygen, a factor proposed to be related to its oxygen-sensing role. The molecular mechanisms for the slow PHD2 reaction with oxygen were investigated using a range of kinetic and biophysical techniques to probe the effects of key active site substitutions. The studies reveal that a conservative substitution to an Fe(II)/H2O binding residue results in 5-fold faster reaction with oxygen, suggesting a role for H2O release from the active site in limiting the ability of oxygen to react with PHD2. This thesis also describes the first transient kinetic studies of FIH. The obtained results show that the rate of the FIH reaction with oxygen was significantly faster than for PHD2. Further, FIH catalyses hydroxylation not only of HIF-α, but also of proteins containing ankyrin repeat domains (ARD). The rate of the FIH reaction with oxygen was shown to be substrate dependent; faster oxygen activation of the reaction in the presence of ARD compared with HIF substrates was observed. Mechanistic studies were performed to investigate a report that PHD2 is involved in the enzymatic oxidation of an oncometabolite (R)-2-hydroxyglutarate (2HG) to give 2OG, in what would be an unprecedented reaction for a 2OG oxygenase. This work found that 2HG does not substitute for 2OG in PHD2 catalysis. Instead, the non-enzymatic transformation of 2HG to 2OG was observed, which could potentially contribute to the reported 2HG-dependent PHD activation in vivo. The biophysical and transient kinetic techniques used for studying the HIF hydroxylases were also applied to study the mechanism of deacetoxycephalosporin C synthase (DAOCS, the enzyme catalysing penicillin N ring expansion). Previously, it has been suggested that the DAOCS mechanism differs from the consensus 2OG oxygenase mechanism. The results described in this thesis provide strong evidence that DAOCS employs the consensus ordered mechanism characteristic of 2OG oxygenases, supporting the proposal that the consensus mechanism is a common feature of the 2OG oxygenase family. Overall, the work described in this thesis is supportive of the proposal that most, if not all, 2OG oxygenases employ a common mechanism. However, the differences in the kinetics of their reaction with oxygen, presented throughout the thesis, suggest that different 2OG oxygenases have different rate-limiting steps. Thus, the kinetics of specific oxygenases may be adapted to their biological function, in particular that of PHD2 as the key cellular O2 sensor.